TINJAUAN HUKUM TENTANG PERLINDUNGAN ANAK DI LUAR KAWIN DALAM PEMBUATAN AKTA KELAHIRAN (STUDI KASUS DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BAU-BAU) - Putri, Yesinta; ALFAHRAL, REZA; M Rizki Mustika Suhartono; Nur, AL Hiday (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the legal protection of children born out of wedlock in the issuance of birth certificates at the Population and Civil Registration Office of Baubau City and to identify the factors that hinder its implementation. This research employed an empirical legal method with a descriptive qualitative approach. Data were collected through interviews, observations, documentation, and literature studies. The results indicate that legal protection for children born out of wedlock has been implemented through birth certificate issuance services based on Law Number 24 of 2013 concerning Population Administration and Law Number 35 of 2014 concerning Child Protection. However, the implementation of legal protection still faces several obstacles, including limited public understanding, unregistered marriages, social stigma, lack of public awareness programs, and administrative constraints. This study concludes that the state has provided legal protection for the identity rights of children born out of wedlock; however, its effectiveness needs to be enhanced through strengthened legal education and improved population administration services.